Effect of aging and brine injection on meat quality characteristics of the one-humped camel (Camelus dromedarius) longissimus muscle - Gamaleldin Mustafa Suliman (Taylor & Francis Group, 2021)
This study was conducted to investigate the effect of wet aging and brine injection on meat quality attributes of the one-humped camel. Both longissimus thoracis muscles of eight male camels were collected; the right muscle of each carcass was used for aging (A) only where no brine (B) injection applied, and the left muscle was brine-injected with 250 mM food-grade CaCl2 at 5% (wt/wt). The aged muscles were cut into steaks, vacuum-packaged, and stored at 2°C for 3, 7, or 10 days. The injected muscles were also treated as the aged muscles. Wet aging had significant effects (p < 0.05) on the ultimate pHu, drip loss (DL), water-holding capacity (WHC), shearing force, and myofibril fragmentation index (MFI). Brine injection also significantly affected (p < 0.05) the ultimate pHu, DL, WHC, and MFI. Therefore, wet aging and brine injection could be applied in a combination to enhance the quality attributes of camel meat.